A System Dynamics Model to Predict the Human Monocyte Response to Endotoxins - Álvarez, Enrique; Toledano, Víctor; Morilla, Fernando; Hernández-Jiménez, Enrique; Cubillos-Zapata, Carolina; Varela-Serrano, Aníbal; Casas-Martín, José; Avendaño-Ortiz, José; Aguirre, Luis A.; Arnalich, Francisco; Maroun-Eid, Charbel; Martín-Quirós, Alejandro; et al. (Frontiers in Immunology, 2017)
System dynamics is a powerful tool that allows modeling of complex and highly networked systems such as those found in the human immune system. We have developed a model that reproduces how the exposure of human monocytes to lipopolysaccharides (LPSs) induces an inflammatory state characterized by high production of tumor necrosis factor alpha (TNFα), which is rapidly modulated to enter into a tolerant state, known as endotoxin tolerance (ET). The model contains two subsystems with a total of 6 states, 7 flows, 2 auxiliary variables and 14 parameters that interact through 6 differential and 9 algebraic equations. The parameters were estimated and optimized to obtain a model that fits the experimental data obtained from human monocytes treated with various LPS doses. In contrast to publications on other animal models, stimulation of human monocytes with super-low-dose LPSs did not alter the response to a second LPSs challenge, neither inducing ET, nor enhancing the inflammatory response. Moreover, the model confirms the low production of TNFα and increased levels of C-C motif ligand 2 (CCL2) when monocytes exhibit a tolerant state similar to that of patients with sepsis. At present, the model can help us better understand the ET response and might offer new insights on sepsis diagnostics and prognosis by examining the monocyte response to endotoxins in patients with sepsis.